DEVELOPING THE KNOWLEDGE OF INDIVIDUALS IN THE ORGANIZATION (BASE ON MATERIALS A BRANCH OF THE STRUGAL ALGERIA FOUNDATION-AL-HASNAWI GROUP - SIDI BEL ABBES) - Каутер Нур Наими; Амина Слама (Экономика, профессия, бизнес)
Djillali Liabes University (Sidi Bel Abbes, Algeria)